The Living Wage in the UK: testing the limits of soft regulation?. (August 2019) - Johnson, Mathew; Koukiadaki, Aristea; Grimshaw, Damian
This article critically evaluates the mixed fortunes of the Living Wage in the UK since its introduction in London nearly 20 years ago. The evidence shows that the gains in hourly pay have been significant, and have been achieved at little or no cost to jobs or working hours. An adequate living wage is therefore a necessary factor in reducing labour market inequality and eradicating in-work poverty. However, the UK case demonstrates that a living wage is not a sufficient factor in the absence of both a coordinated approach for universal implementation and linkages with effective collective bargaining. Poor coordination explains the very low proportion of low-wage workers covered by a voluntary Living Wage. Weak links with collective bargaining mean that even where a Living Wage is introduced by a low-wage employer, further positive wage ripple effects (e.g. by sustaining wage differentials) are rare. The argument advanced here is that while employers increasingly perceive voluntary accreditation with the Living Wage Foundation as an important symbol of 'business ethics', the Living Wage remains a relatively isolated wage-setting instrument in the UK. This is the result not only of the voluntarist nature of the campaign but also of the limited scope for direct interaction with other wage-setting mechanisms in the UK, despite evidence of positive complementarity between a living wage and collectively bargained pay structures. The article concludes by exploring different mechanisms through which the Living Wage could be extended and embedded across low-wage labour markets.